Peatland forests are the least diverse tree communities documented in Amazonia, but contribute to high regional beta‐diversity. Issue 8 (16th January 2018) - Draper, Frederick C.; Honorio Coronado, Eurídice N.; Roucoux, Katherine H.; Lawson, Ian T.; A. Pitman, Nigel C.; A. Fine, Paul V.; Phillips, Oliver L.; Torres Montenegro, Luis A.; Valderrama Sandoval, Elvis; Mesones, Italo; García‐Villacorta, Roosevelt; Arévalo, Fredy R. Ramirez; et al.
Abstract : Western Amazonia is known to harbour some of Earth's most diverse forests, but previous floristic analyses have excluded peatland forests which are extensive in northern Peru and are among the most environmentally extreme ecosystems in the lowland tropics. Understanding patterns of tree species diversity in these ecosystems is important both for quantifying beta‐diversity in this region, and for understanding determinants of diversity more generally in tropical forests. Here we explore patterns of tree diversity and composition in two peatland forest types – palm swamps and peatland pole forests – using 26 forest plots distributed over a large area of northern Peru. We place our results in a regional context by making comparisons with three other major forest types: terra firme forests (29 plots), white‐sand forests (23 plots) and seasonally‐flooded forests (11 plots). Peatland forests had extremely low (within‐plot) alpha‐diversity compared with the other forest types that were sampled. In particular, peatland pole forests had the lowest levels of tree diversity yet recorded in Amazonia (20 species per 500 stems, Fisher's alpha 4.57). However, peatland pole forests and palm swamps were compositionally different from each other as well as from other forest types in the region. Few species appeared to be peatland endemics. Instead, peatland forests were largely characterised by a distinctive combination of generalist species and species previously thought to be specialists of other habitats, especially white‐sand forests. We suggest that the transient nature and extreme environmental conditions of Amazonian peatland ecosystems have shaped their current patterns of tree composition and diversity. Despite their low alpha‐diversity, the unique combination of species found in tree communities in Amazonian peatlands augment regional beta‐diversity. This contribution, alongside their extremely high carbon storage capacity and lack of protection at national level, strengthens their status as a conservation priority.